Cultural and morphological characterization of Colletotrichum capsici the causal organism of anthracnose of chilli - Kamble, H N; Dhutraj, D N (Indian Journal of Plant Protection, 2020)
Sixteen isolates of Colletotrichum capsici were collected from different chilli growing areas of Maharashtra and their pathogenicity was proved under laboratory conditions. Maximum mycelial growth (87.00 mm) was recorded with CcA isolate followed by CcP (86.70 mm), CcJ (84.28 mm), CcH (83.37 mm), CcN (79.89 mm), CcL (75.80 mm) and CcB (74.91 mm). Colony colour was dark brown in CcA and CcP isolates whereas, it was gray with white mycelium in CcJ and CcB isolates. CcN and CcH showed black colony colour with grayish mycelium. Colony colour of CcO isolate was whitish creamy while, isolate CcL produced grayish white colony. Topography of growth on PDA medium was flat in CcN, CcA and CcO isolates and rose in case of CcJ, CcH, CcP, CcB and CcL isolates. Largest sized conidia (27.32 × 2.89 µm) were produced by the isolate CcN followed by CcA (25.52 × 3.54 µm) and CcP (25.12 × 2.57 µm). Conidia of all the isolates were falcate, blunt to narrow at ends with oil globuse at centre. Maximum length of setae (116.23 µm) was recorded in CcA isolate followed by CcB (112.34 µm), CcO (110.77 µm), CcP (108.92 µm), CcN (108.1 µm), CcJ (103.87 µm) and CcH (101.78 µm). All the isolates produced dark brown setae with smooth, septate, rigid, hardly swollen at the base and slightly tapered towards the paler acute apex. Among the different media tested, better growth and sporulation was recorded with Richard’s agar (88.94 mm), Czapek’s dox agar (88.53 mm), Oat meal agar (87.53mm) and Sabouroud agar (87.31 mm).